Threats to Our Ocean Heritage: Potentially Polluting Wrecks - Brennan, Michael L.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This open access volume focuses on the environmental hazards and cultural significance of Potentially Polluting Wrecks (PPWs), and how mitigation efforts have assisted in documenting and preserving the history of these sites. It is an important resource on the subject of Potentially Polluting Wrecks that synthesizes previously published information that was not academically or scientifically produced. This includes numerous international studies of shipwreck databases and threats posed by world war wrecks containing oil and other hazardous materials that could spill. This book evaluates these materials and presents new analyses and investigations with modern technology that assist in locating, documenting, and remediating polluting wreck sites. Consequently, this volume calls for increased ocean exploration missions to locate sunken merchant vessels that may pose pollution hazards and site assessments to determine any potential risks. This book is of interest to government officials, educators, archaeologists and practitioners working in the field of underwater archaeology.
Foreword (Mark J. Spalding) -- 1. Potentially Polluting Wrecks: An Introduction (Michael L. Brennan) -- 2. Potentially Polluting Wrecks and the Legal Duty to Protect Our Ocean Heritage (Mariano J. Aznar, Ole Varmer) -- 3. Environmental Impact and Modeling of Petroleum Spills (Matt Horn, Deborah French-McCay, Dagmar Schmidt Etkin) -- 4. Corrosion Processes of Steel-Hulled Potentially Polluting Wrecks (Robert Glover) -- 5. From Desktop to Dive: Assessing the Pollution Potential of SS Fernstream, USNS Mission San Miguel and SS Coast Trader (James P. Delgado) -- 6. Managing Potentially Polluting Wrecks in the United Kingdom (Polly Georgiana Hill, Matthew Skelhorn, Freya Goodsir) -- 7. Polluting Wrecks in the Baltic Sea (Benedykt Hac) -- 8. Potentially Polluting Wrecks in the Blue Pacific (Matthew Carter, Ashley Meredith, Augustine C. Kohler, Bradford Mori, Ranger Walter) -- 9. Satellite Detection and the Discovery of Bloody Marsh (Michael L. Brennan, Geoffrey Thiemann, William Jeffery) -- 10. Searching for a Lost PPW: SS William Rockefeller (John Detlie) -- 11. Assessment Methodologies for Potentially Polluting Wrecks: The Need for a Common Approach (Mark Lawrence, Stuart Leather, Simon Burnay) -- 12. Concluding Statement (Joao Sousa, Benjamin Ferrari, Michael L. Brennan, Ole Varmer).
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Underwater archaeology; Cultural property -- Protection; Historic preservation; Oceanography; Maritime Archaeology; Conservation and Preservation; Ocean Sciences